Raising Awareness of Stereotyping Through Collaborative Digital Storytelling: Design for Change with and for Children. Issue 157 (January 2022) - Rubegni, Elisa; Landoni, Monica; Malinverni, Laura; Jaccheri, Letizia
Highlights: to spread insight on our approach and support the HCI community to replicate it to challenge the negative effect stereotypes, to provide knowledge on how gender stereotype awareness could be raised among children through the collaborative creation of DST. Abstract: The purpose of our research is to use design as a mean to support children becoming more aware of stereotypes in their own artefacts. We have been facing this challenge leveraging on Digital StoryTelling (DST) as a powerful instrument to detect children's beliefs and values including those connecting to gender. In addition, considering the role of social interactions in creating and reproducing gender stereotypes in children we have been focusing on the collaborative creation of digital stories to investigate stereotypes as a cultural product. The goal of the paper is to give an account of our process of digging into this topic and our design pathway in developing and assess a DST prototype directed to raise children's awareness. Our work main contribution is to spread insight on our approach and support the HCI community to replicate it to challenge the negative effect of stereotypes, and to provide new knowledge on how gender stereotype awareness could be raised among children through the collaborative creation of DST. As a final research contribution we provide a set of design recommendations to address the design of a collaborative DST tool for raising stereotype awareness.